The impact of DNA methylation on the stability and dynamics of i-motif in the ILPR promoter region - Ďurinová, Eva (Jihočeská univerzita, 2016)
The stability of i-motif structure in the promoter of the insulin gene was investigated by circular dichroism and single-molecule fluorescence resonance energy transfer. The main factor studied was the cytosine methylation and its location in the DNA sequence. Also the molecular crowding effect was examined. In addition, i-motif folding kinetics were investigated by the single molecule method.
The impact of DNA methylation on the stability and dynamics of i-motif in the ILPR promoter region
Keywords: i-motif; cytosine methylation; ILPR; DNA folding; single-molecule FRET